Pembuatan Produk Multimedia Sebagai Media Informasi Dan Dokumentasi Pertanian Di Balai Besar Pengkajian Dan Pengembangan Teknologi Pertanian: Creating Multimedia Products as Agricultural Information and Documentation Media at the Indonesian Center for Agricultural Technology Assessment and Development - Nita Qonitah Desy Ayu Sari; Aep Setiawan; Elya Nurwullan (IPB University, 2018)
ABSTRACT The Indonesian Center for Agricultural Technology Assessment and Development (BBP2TP) is a Research, study and development center for agricultural technology that houses 31 Agricultural Technology Assessment Centers (BPTP) in regions that produce location-specific agricultural technology. BBP2TP is a means to convey information about agricultural products from farmers, researchers and extension workers to the public by using electronic media in the form of news, articles, powerpoint slides and printed media in the form of brochures and books in terms of providing information and documentation. Based on this, several multimedia products were made such as posters, video tutorials, and video documentation of activities.The method used in making this multimedia product was made according to what was done during the Field Work Practices (PKL) at BBP2TP both when working on posters, video tutorials and video documentation of activities. There are four stages: observation, data collection, editing, and testing. ABSTRAK Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian (BBP2TP) adalah Balai penelitian, pengkajian dan pengembangan teknologi pertanian yang menaungi 31 Balai Pengkajian Teknologi Pertanian (BPTP) di daerah yang menghasilkan teknologi pertanian spesifik lokasi. BBP2TP menjadi sarana untuk menyampaikan informasi tentang produk pertanian dari petani, peneliti dan penyuluh kepada masyarakat dengan menggunakan media elektronik berupa berita, artikel, slide powerpoint dan media cetak berupa brosur dan buku dalam hal pemberian informasi dan dokumentasi. Berdasarkan hal tersebut, maka dibuatlah beberapa produk multimedia seperti poster, video tutorial, dan video dokumentasi kegiatan.Metode yang digunakan dalam pembuatan produk multimedia ini dibuat sesuai dengan apa yang dilakukan saat Praktik Kerja Lapang (PKL) di BBP2TP baik saat mengerjakan poster, video tutorial maupun video dokumentasi kegiatan. Terdapat empat tahapan yaitu observasi, pengumpulan data, proses penyuntingan, dan pengujian.